The Timing of Climate Agreements under Multiple Externalities - Robert C. Schmidt; Roland Strausz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2011)
We study the potential of cooperation in global emission abatements with multiple externalities. Using a two-country model without side-payments, we identify the strategic effects under different timing regimes of cooperation. We obtain a positive complementarity effect of long-term cooperation in abatement on R&D levels that boosts potential bene?t of long-term cooperation and a redistributive effect that destabilizes long-term cooperation when countries are asymmetric. We show that whether and what type of cooperation is sustainable, depends crucially on the kind rather than on the magnitude of asymmetries.
urn:nbn:de:bvb:19-epub-13188-3
Keywords: D62; F53; H23; Q55; 330; climate treaty; timing of cooperation; multiple externalities; long-term commitment; Klimaschutz; Umweltabkommen; Zeit; Internationale Zusammenarbeit; Externer Effekt; Umwelttechnik; Innovation; Theorie